Rancang Bangun Sistem Informasi Recruitment Berbasis Web Bagi Karyawan Baru - Abdul Hamid Arribathi; Lisda Anggraeni; Riska Putri Gestiarie (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
n processing employee recruitment data, it still uses a manual system so that the company experiences several problems in searching for applicant files. So we need a system that can handle the recruitment of new employees that can support the performance of a company. In this study, researchers used SWOT analysis, PHP (Hypertext Preprocessor) was used for the programming language, while the software used for the database server system was MySQL, and XAMPP. With this employee recruitment system, it can make it easier for applicants to be able to directly access the application files on the website, as well as make it easier for HRD in the process of selecting new employees.